Integrated transcriptomic and metabolomic analyses of the molecular mechanisms of two highland barley genotypes with pyroxsulam responses - Weng, Hua; Yan, Jiahui; Guo, Liangzhi; Chen, Hongyu (Frontiers in Plant Science, 2022)
Highland barley is one of the few crops that can be grown at high elevations, making it a key resource within the Tibet Plateau. Weeds are a significant threat to highland barley production, and new herbicides and tolerant barley varieties are needed to control this ever-growing problem. A better understanding of existing herbicide resistance mechanisms is therefore needed. In this study, transcriptomic and metabolomic analyses were used to identify molecular and physiological changes in two highland barley genotypes with differing sensitivities to the herbicide pyroxsulam. We identified several stress-responsive metabolites, including flavonoids and antioxidants, which accumulated to significantly higher levels in the pyroxsulam-resistant genotype. Additionally, we found key genes in both the flavonoid biosynthesis pathway and the antioxidant system that were up-regulated in pyroxsulam-resistant barley. This work significantly expands on the current understanding of the molecular mechanisms underlying differing pyroxsulam tolerance among barley genotypes and provides several new avenues to explore for breeding or engineering tolerant barley.